Indeks Beban Pencemar Sebagai Penentu Tingkat Pencemaran Pada Lahan Bekas Pertambangan Emas Tanpa Izin - Surya Sumando Putra Panggabean; Zuli Rodhiyah; Freddy Ilfan; Mahya Ihsan (Yayasan Literasi Sains Indonesia, 2022)
Sarolangun Regency is a district that has the potential for gold metal mineral natural resources. This potential causes many illegal gold mining activities (PETI) in the area. It is also suspected that PETI activities can cause environmental damage and pollution in the activity area and downstream from the PETI location. Environmental pollution that occurs is caused by the disposal of gold processing waste (tailings) into water bodies and groundwater. Waste generated from gold mining activities mainly contains mercury (Hg) and lead (Pb). The purpose of this study was to analyze the level of heavy metal pollutants (Hg and Pb) using the contamination factor (CF), the pollutant load index (PLI), and the geoaccumulation index (I_geo) on former PETI in Sarolangun Regency. The sampling technique was carried out by a purposive sampling technique and the sample taken was soil. Heavy metal concentration data will be calculated using the CF, I_geo, and PLI index formulas. Hg concentrations were 0.86 mg/kg, 0.77 mg/kg, and 0.80 mg/kg in three sampling areas, and lead concentrations were 0.51 mg/kg, 0.54 mg/kg, and 0.53 mg/kg. Based on the analysis of CF calculations and I_geo, Hg(mercury) has more potential to become a pollutant at the study site (CF>6), (2<I_geo<3). On the other hand, the study site was not polluted by lead based on the CF value and geoaccumulation index. The overall PLI calculation of Hg and Pb stated that the research location was not included in the polluted category with a PLI value <1.